Effectiveness of final income tax imposition on MSME performance - Djuminah, Djuminah; Andreas Catur Restu Kurniadi (Jurnal Ekonomi, 2024)
The research is intended to determine the effectiveness of various tax regulations that have been issued as incentives for Micro, Small and Micro Enterprises (MSME) taxpayers, measured from the increase in corporate value and tax payments. The research uses the Mann-Whitney U Test of IBM SPSS Statistics version 27, a non-parametric test that is used to compare two sample means that come from the same population, and used to test whether two sample means are equal or not. Differential tests are conducted on Taxpayers using a certain gross turnover and Taxpayers do not use gross turnover in the period 2015 – 2022 on taxpayers registered at the Regional Office of DJP Central Java II The results of the study show that in the short-term range policy implementation (2015-2017) have no significant difference between taxpayers who use a certain gross turnover and taxpayers who do not use gross turnover. Meanwhile, different results were shown in the long-term analysis (2015 – 2022), where the conclusions showed that there were significant differences, where non-MSME taxpayers experienced a higher increase in performance compared to MSME taxpayers. With these results, it can be concluded that providing PPh incentives for MSMEs through the implementation of PP no. 46 of 2013, PP no. 23 of 2018 and PP no. 55 of 2022 turns out to be ineffective in improving the performance of MSMEs. The research has limitations in access to the observed data, the data samples are only limited to taxpayers registered in the Regional Office of DJP Central Java II and the 2015 - 2022 tax year. Another limitation of the research is that it does not take into other external factors, namely the Covid-19 pandemic in the period 2020 – 2021. Researchers hope that the research results can be one of the considerations in evaluating the effectiveness of implementing various PPh incentives for MSME taxpayers. Meanwhile, for taxpayers, the results of the research can be used as material for consideration in planning related to company tax planning.